2004
DOI: 10.1038/sj.ijo.0802754
|View full text |Cite
|
Sign up to set email alerts
|

Regular participation in sports is associated with enhanced physical fitness and lower fat mass in prepubertal boys

Abstract: OBJECTIVE:To study the effect of physical activity on whole body fat (BF), its regional deposition and the influence of body fatness on physical performance in prepubertal children. DESSIGN: Cross-sectional study. SUBJECTS: A total of 114 boys (9.471.5 y, Tanner I-II), randomly sampled from the population of Gran Canaria (Spain), 63 of them physically active (PA, at least 3 h per week during the previous year) and 51 nonphysically active (non-PA). MEASUREMENTS: Body composition (DXA), anthropometric variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
103
0
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 51 publications
18
103
0
5
Order By: Relevance
“…Data from the Swedish part of the European Youth Heart Study (EYHS), a schoolbased, cross-sectional study of risk factors for future CVD in a random sample of children (9-10 years old) and of adolescents (15-16 years old), 21 indicate that those individuals having a high cardiorespiratory fitness level also have significantly lower total adiposity, as measured by skinfold thicknesses (Figure 2). 22 When total fatness was assessed by a reference method, that is, Dual Energy X-ray Absorptiometry, a similar inverse association was found in Spanish 24 and North American 25 children. Cardiorespiratory fitness has shown a stronger association with total adiposity, as measured by skinfold thicknesses, than other physical fitness components such as muscular fitness, speed/agility, flexibility or motor coordination.…”
Section: Physical Fitness and Health Outcomesmentioning
confidence: 69%
“…Data from the Swedish part of the European Youth Heart Study (EYHS), a schoolbased, cross-sectional study of risk factors for future CVD in a random sample of children (9-10 years old) and of adolescents (15-16 years old), 21 indicate that those individuals having a high cardiorespiratory fitness level also have significantly lower total adiposity, as measured by skinfold thicknesses (Figure 2). 22 When total fatness was assessed by a reference method, that is, Dual Energy X-ray Absorptiometry, a similar inverse association was found in Spanish 24 and North American 25 children. Cardiorespiratory fitness has shown a stronger association with total adiposity, as measured by skinfold thicknesses, than other physical fitness components such as muscular fitness, speed/agility, flexibility or motor coordination.…”
Section: Physical Fitness and Health Outcomesmentioning
confidence: 69%
“…Results from cross-sectional and longitudinal studies also indicated that participation in at least 3 h per week of extracurricular physical activities and sport competitions is associated with less body fat mass (measured by DXA) in prepubertal children compared with children who do not participate in sports regularly. 43 Furthermore, those children who regularly participated in sports activities at least 3 h per week during 3 years were more protected against total and regional, especially central fat mass accumulation. 44 It is important to consider when interpreting the findings from this study that because of the study design (crosssectional) it is not possible to infer a causal relationship between PA and body fatness.…”
Section: Discussionmentioning
confidence: 98%
“…[18][19][20][21][22][23][24][25] However, some of these studies were conducted with a small number of subjects, whereas others included children and adolescents in the same analyses. It has also been reported that overweight as well as obese children showed a lower physical fitness than normal children.…”
Section: Discussionmentioning
confidence: 99%